Virtual Reality In Enhancing Internet-Based Education - Su, Moon Ting (1998)

(untitled)
Until recently, Internet-based education is fundamentally two-dimensional (2-D). This difference from the three-dimensional (3-D) world that human beings experience and learn provokes that 3-D learning environments should be included into the Internet-based education. It is envisaged that Virtual Reality (VR) has the capability to provide for the 3-D learning environments. The objectives of this study are to investigate the capability of VR in enhancing Internet-based education and to investigate the process of VR model or Virtual Environment (VE) development. As Virtual Reality Modeling language (VRML) is the non-proprietary 3 -D format to represent VR on the Internet and its current version (2.0) enables dynamic, interactive models to be developed these